IMPLEMENTASI MEDIA MOTARO BERBASIS TPACK PADA PEMBELAJARAN IPS UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Kardiana Zendha Avalentina; Adi Tri Atmaja (Universitas Tribhuwana Tunggadewi, 2024)
The purpose of this research is to improve students learning motivation by using TPACK-based MOTARO media in social studies subjects. The type of research method is classroom research which is carried out for 2 cycles. Data analysis was carried out through interviews, observations, questionnaires and documentation to see the level of students learning motivation after using TPACK-based MOTARO media in social studies subjects. The results of observing student motivation obtained a score percentage of 71%, including the high motivation category, and at the second meeting using media, the average class obtained a score percentage of 82%, including the very high motivation category. Then it was obtained through a learning motivation questionnaire that students got the class average score at the first meeting with a percentage of 74% which was included in the high motivation category and at the second meeting there was an increase with the class average with a percentage of 88% which was included in the very high motivation category. So, from the results of the questionnaire and observations obtained, the implementation of TPACK-based MOTARO media in social studies subjects can increase students learning motivation.